A discourse analysis of Melengkan at a Gayonese wedding ceremony - Irama Jaya; Bukhari Daud (Studies in English Language and Education, 2017)
Melengkan is a special form of the Gayonese language which is spoken in poetry, lyrics, and proverbs. This study investigated its use as poetry specifically in wedding ceremonies held in Gayo, Aceh, Indonesia. The data was collected by observations and a video-recording of a traditional Gayonese wedding ceremony, as well as from interviews with melengkan speakers. We described and analyzed the context of the use of melengkan, the form of melengkan, and the cultural values conveyed through melengkan used in the wedding ceremony. The findings showed that there were six types of melengkan: Melengkan Turun Caram, Melengkan Beguru, Melengkan Munyerah Rempele, Melengkan Munerime Rempele, Melengkan Munyerah Munenes and Melengkan Munerime Munenes. The values of melengkan are for remembrance of local knowledge, warnings from customary philosophy, warnings from religion, and also for giving advice and recall the history and beauty of melengkan speech. The context of using melengkan is to perpetuate and reflect cultural values, namely, politeness, respect, speaking softly, friendliness and resoluteness. These findings imply the importance of conserving melengkan as part of the Gayonese culture in every part of their life.